ANALISIS IMPLEMENTASI FUNGSI MANAJEMEN DALAM PENANGANAN COVID-19 DI RSUD Dr.H. IBNU SUTOWO BATURAJA TAHUN 2021 - Sopi Susilawati (JURNAL KESEHATAN INDRA HUSADA, 2021)
Introduction: Handling Covid-19 is a good step in minimizing the risk of infection in officers and controlling the risk of infection in health care facilities that are a concern in the current Covid-19 pandemic. The purpose of this study was to determine the implementation of the handling of Covid-19 at RSUD Dr.H. Ibnu Sutowo Baturaja seen from the theory of management functions Method: The design of this research is a qualitative descriptive analysis study which was carried out in June 2021. There were 6 informants from the Covid-19 handling team at RSUD Dr.H. Ibn Sutowo Baturaja. The sampling method of this research is purposive sampling. Data were collected through interviews and observations. Result: planning followed the policies of the central and local governments, several things of concern were the planning of trained nurses for intensive care, provision of RT-PCR examination laboratories and isolation rooms or Intensive Care Units (ICU) negative pressure. Organizing, has formed the Rapid Response Team for the Covid-19 outbreak with members from various professions whose duties and functions have been divided. Actuating, providing direction and motivation so that planning goes according to plan. Controlling, periodic evaluation monitoring is carried out. Conclusion: the implementation of the Covid-19 handling management function is carried out following the policies of the central and regional governments.